THE SIGNIFICANCE OF BILINGUAL DICTIONARIES IN TEACHING ENGLISH AT SCHOOL, LYCEUM, COLLEGE AND HIGHER EDUCATIONAL ESTABLISHMENTS - Ruzimov, Sh. (FAN va JAMIYAT, 2018)
In the article compiling principles of English-Uzbek and Uzbek-English dictionaries were critically investigated and there were given practical recommendations for improving their role in teaching English at schools, lyceums, colleges and higher educational establishments.